Coexistence in hiking to the Plaza de Armas told by a multimedia - Avila Portuondo, Ailet Maria; Bauye Plana , Alexey; Portuondo Barbón , Ana Maria (Revista Minerva, 2022)
The use of computer resource in the educational field has brought with it a better coexistences for teachers and students. The objective of this work is to design a multimedia in correspondence with the program of the subject History and hiking activities. To solve the stated objective, materials were used such as: Mediator 8.0 Exp. Applications and Adobe Photoshop CC for image processing and theoretical level methods: analytical – synthetic, and modeling. Results and discussion: multimedia was developed for the preparation of students in significant aspects that they will see in museums and historical spaces of the Plaza de armas and its surroundings. Conclusions: a multimedia with a friendly environment that is easy to handle that allows combining various materials of different extensions (texts, images, videos and animations) that contributes to cultural, ethical and aesthetic, training, stimulates a taste for history and the discovery of places interesting.